2017
DOI: 10.3389/feduc.2017.00021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Capability and Student Self-regulation: The Challenge of Preparing Teachers

Abstract: Research over several years has found that "effective learners tend to monitor and regulate their own learning and, as a result, learn more and have greater academic success in school" (Andrade, 2010, p. 90). In New Zealand primary schools, the primary purpose of assessment and evaluation is to improve students' learning and teachers' teaching as both respond to the information it provides. To bring this purpose to fruition, teachers need to be educated to facilitate genuine engagement by learners in assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Recommendation was made for closer liaisons between schools, where practicums were undertaken, and universities in order for enhanced alignments between PSTs' beliefs and praxis (Smith et al, 2014). Emphasis should therefore be given to the ways in which PSTs' assessment capability is developed in both the university and school environments (Hill et al, 2017).…”
Section: Context Of Ite Practice -A Crisis Of Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendation was made for closer liaisons between schools, where practicums were undertaken, and universities in order for enhanced alignments between PSTs' beliefs and praxis (Smith et al, 2014). Emphasis should therefore be given to the ways in which PSTs' assessment capability is developed in both the university and school environments (Hill et al, 2017).…”
Section: Context Of Ite Practice -A Crisis Of Controlmentioning
confidence: 99%
“…Moreover, while it is clear that policy from a range of contexts focuses on the development of student agency (Klenowski, 2009;Booth, Hill, & Dixon, 2014), it is less apparent that this is in evidence in classrooms (Dixon et al, 2011;Flockton, 2012). It is also unclear the degree to which PSTs are purposefully mentored to gain experience in classrooms pertaining to assessment capability (Hill, Ell, & Eyers, 2017). This introduces another level of complexity for PSTs whose understandings of assessment practices are strongly influenced by those of their mentor teachers; there is a reliance on the demonstrations of practice they see from mentor teachers in the day to day of their practicum classrooms.…”
Section: Co-constituting Assessment Identitiesmentioning
confidence: 99%
“…Hill et al (2017) found negative feelings and attitudes toward assessment, and Deneen and Brown (2016) revealed polarized affective conceptions of assessment among preservice teachers. Hill et al (2017) described how they employ the same assessment strategies they experienced themselves as pupils (see also Hamodi et al, 2016), tend to see assessment as synonymous with the testing culture, and generally abandon formative assessment. To sum, newly qualified teachers' assessment literacy (TAL) level is low.…”
Section: Introductionmentioning
confidence: 98%
“…Difficulties with common assessment responsibilities, basic conceptions, and the purposes of assessment are reported (Mellati and Khademi, 2018). Hill et al (2017) found negative feelings and attitudes toward assessment, and Deneen and Brown (2016) revealed polarized affective conceptions of assessment among preservice teachers. Hill et al (2017) described how they employ the same assessment strategies they experienced themselves as pupils (see also Hamodi et al, 2016), tend to see assessment as synonymous with the testing culture, and generally abandon formative assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem that we face is how to prepare students, most of whom are "fresh graduates" to study as a "whole" person, and develop their capabilities (Staron, 2011) to live in the future in the sense that as future teacher/lecturer, they can also develop the capabilities of their students (Hill, Ell, & Eyers, 2017) since there is a tendency that the teacher or lecturer teaches their students according to their experience of how they were taught previously in university.…”
mentioning
confidence: 99%